Innovation of Arabic Speaking Skill Development with Comic Media at MTs Mabdaul Ma'arif Jember - Fina Aunul Kafi; Zulfa Faridhatul Husna (INAIFAS PRESS, 2022)
Speaking competence (mahārah al-kalām) is a basic skill that students need to master in learning Arabic. The use of comics learning media can help students improve this competence. This research aimed to describe the implementation of mahārah al-kalām learning using comic media which was applied at MTs Mabdaul Ma'atif Jombang Jember. This study used qualitative research methods because the object of research focused on the learning process of mahārah al-kalām with comic media. The results of the application of comic media showed that 7.14% of students were very able to improve the competence of mahārah al-kalām by using comic media, 89.29% were classified as capable, and 3.57% of students were less able based on assessment indicators. This media can be used as an alternative in learning Arabic to hone students' Arabic speaking skills.